Seismic Response of Irregular Triangular Alluvial Valleys under Shear Waves Using Spectral Elements - Saeed Hosseinpour; Jafar Najafizadeh (Salehan Institute of Higher Education, 2018)
The present study investigates seismic response problems of triangular uniform irregular alluvial valleys under shear waves using a finite element spectral method. Alluvial valleys; affect the shape and properties of alluvial materials on the response and seismic behavior of the valley surface due to the geometry conditions. Therefore this study aims to illustrate the plots and magnitude of amplification values for irregular alluvial valleys in a two-dimensional triangular manner, with the characteristics of homogeneous alluvial materials and different geometric characteristics. The analysis in the time domain was performed based on the finite element method of the spectral element (SFEM) using NASEM software, developed by Najafizadeh. The valleys are analyzed with the slope angles of 15, 30, 45 and 60 degrees on one side and in opposite directions with a slope of 45 degrees and with a maximum depth of 50 meters for the alluvial valley. The horizontal amplification curves in the alluvial valley's points from the analysis reach a maximum value at a given frequency, which can be an ideology for determining the frequency of irregular triangular alluvial valleys under different slope valley angles. The results of natural valley frequencies indicate that with decreasing slope of the valley, the natural frequency of the valley decreases, as well as amplification plots are related to the slope of the valley.